English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-08 21:56:31 · 4 answers · asked by lucignolo 2 in Science & Mathematics Mathematics

Y=e^(bx^2)

and Ln(x+y) = e^(x/y)

2007-03-08 22:34:08 · update #1

4 answers

y = e^(bx^2)
dy/dx = (2bx)(e^(bx^2))

Ln(x+y) = e^(x/y)
d/dx Ln(x+y) = d/dx (e^(x/y))
1/(x+y) + 1/(x+y) dy/dx = (1/y)e^(x/y) - (x/y^2)e^(x/y) dy/dx
1/(x+y) dy/dx + (x/y^2)e^(x/y) dy/dx = (1/y)e^(x/y) - 1/(x+y)
[1/(x+y) + (x/y^2)e^(x/y)] dy/dx = (1/y)e^(x/y) - 1/(x+y)
dy/dx = [(1/y)e^(x/y) - 1/(x+y)] / [1/(x+y) + (x/y^2)e^(x/y)]

2007-03-08 22:45:06 · answer #1 · answered by seah 7 · 1 0

Y= e^bx^2

d/dxY=2bxe^bx^2 (using chain rule + remember that d/dx e^x =e^x or d/dx e^ax=ae^ax

Ln(x+y) =e ^x/y?
if u want d/dx then d/dx ln(x+y)=(1/(x+y) )(dy/dx) ...(chain rule)

and d/dx e ^x/y?=(1/y + (-x/y^2)dy/dx)e ^x/y?....(chain rule)

just equate the 2 and solve for dy/dx .

2007-03-09 06:12:05 · answer #2 · answered by hiphop 2 · 0 0

In the first question you haven't indicated with either brackets or multiplication sign so it's difficult to see what you are actually asking

2007-03-09 06:07:46 · answer #3 · answered by hey mickey you're so fine 3 · 0 0

y= e^bx^2

write down

y'=(2bx)*e^(bx^2)

Ln(x+y) =e ^(x/y)
let partial wrt to x =fx'
let partial wrt to y =fy'

ln(x+y) -e^(x/y)=0

fx'= 1/(x+y)-e^(x/y)/y
fy'= 1/(x+y)+x*e^(x/y)/y^2

dy/dx= -fx'/fy'
{fx'+fy'(dy/dx)=0,standard
relationship}
therefore,
dy/dx={e^(x/y)/y-1/(x+y)}
/{x*e^(x/y)/y^2+1/(x+y)}

i hope that this helps

2007-03-09 11:26:51 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers